2011
DOI: 10.1371/journal.pone.0016265
|View full text |Cite
|
Sign up to set email alerts
|

Visual Stability and the Motion Aftereffect: A Psychophysical Study Revealing Spatial Updating

Abstract: Eye movements create an ever-changing image of the world on the retina. In particular, frequent saccades call for a compensatory mechanism to transform the changing visual information into a stable percept. To this end, the brain presumably uses internal copies of motor commands. Electrophysiological recordings of visual neurons in the primate lateral intraparietal cortex, the frontal eye fields, and the superior colliculus suggest that the receptive fields (RFs) of special neurons shift towards their post-sac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 96 publications
(104 reference statements)
4
13
0
Order By: Relevance
“…However, it was demonstrated that the TAE decreased gradually at the present, presaccadic location of the adaptor and simultaneously increased at the future, postsaccadic location of the adaptor when observers were about to make a saccade. Similar findings were reported for the motion after-effect [16], and this apparent presaccadic transfer of visual after-effects has been interpreted within the predictive remapping framework. In other words, immediately before saccade onset, RFs of the adapted neuronal population are thought to shift along a vector equal to the impending saccade, and thus a decreased after-effect is observed at the presaccadic adaptor location.…”
Section: Predictive Remapping In Humanssupporting
confidence: 85%
“…However, it was demonstrated that the TAE decreased gradually at the present, presaccadic location of the adaptor and simultaneously increased at the future, postsaccadic location of the adaptor when observers were about to make a saccade. Similar findings were reported for the motion after-effect [16], and this apparent presaccadic transfer of visual after-effects has been interpreted within the predictive remapping framework. In other words, immediately before saccade onset, RFs of the adapted neuronal population are thought to shift along a vector equal to the impending saccade, and thus a decreased after-effect is observed at the presaccadic adaptor location.…”
Section: Predictive Remapping In Humanssupporting
confidence: 85%
“…At the same time, interestingly, the aftereffect for stimuli presented at the fovea-the retinal location previously occupied by the adaptor-declined from previous levels. Biber and Ilg (2011) reported similar findings using adaptation to motion rather than tilted gratings. These findings have been proposed as evidence that predictive remapping affects perceptual experience.…”
supporting
confidence: 55%
“…Turi and Burr (2012) showed that two forms of motion aftereffects (MAEs), which probably act at different neural levels of processing, are observed in different reference frames. In other words, when saccades are involved between adaptation and test stimuli, lower-level adaptation such as the classic MAE, in which prolonged exposure to a moving stimulus makes a stationary stimulus viewed subsequently appear to move in the opposite direction, is strictly encoded in retinotopic coordinates that shift with each eye movement (Biber & Ilg, 2011;Boi, Ogmen, & Herzog, 2011;Cavanagh et al, 2010;Knapen et al, 2009;Wenderoth & Wiese, 2008). In contrast, higher-level adaptation such as the positional MAE, in which the apparent position changes by adaptation to motion, is encoded in spatiotopic screen-based coordinates.…”
Section: Characteristics Of Visual Motion Priming and Its Relation Tomentioning
confidence: 99%